Exome sequencing identifies a de novo mutation of CTNNB1 gene in a patient mainly presented with retinal detachment, lens and vitreous opacities, microcephaly, and developmental delay: Case report and literature review. Issue 20 (May 2017) - Li, Niu; Xu, Yufei; Li, Guoqiang; Yu, Tingting; Yao, Ru-en; Wang, Xiumin; Wang, Jian
Abstract: Rationale: The CTNNB1 (β-catenin) gene is well known for its crucial role in cell adhesion and the Wnt-signaling pathway. Previous studies have shown that gain-of-function mutations in the CTNNB1 gene contribute to the occurrence and development of a variety of carcinomas in humans. Recently, de novo, heterozygous, loss-of-function mutations of the CTNNB1 gene were found that partially explain intellectual disability in some patients. Other major clinical symptoms in these patients included microcephaly, abnormal facial features, motor delays, speech impairments, and deformities of the hands and feet. In addition, approximately 75% of these patients had mild visual defects, such as astigmatism, hyperopia, or strabismus Patient concerns: A 15-month-old Chinese boy, presenting with retinal detachment, lens and vitreous opacities, hypertonia of the extremities, mild thumb adduction, microcephaly, and developmental delay, is described. Targeted gene sequencing using an ophthalmic gene panel was performed to test for familial exudative vitreoretinopathy; however, the pathogenic gene was not found. Interventions: Genomic DNA analysis was performed to search for causing mutations. Diagnoses and outcomes: Whole-exome sequencing revealed a novel nonsense variation in exon 11 of the CTNNB1 gene (c.1672C>T, p.Gln558X). Sanger sequencing of the patient and his parent confirmed this mutation and demonstrated it to be de novo. To the best of our knowledge, this is the first case report of a loss-of-function mutation of the CTNNB1 gene in an Asian population. Lessons: Severe ophthalmic phenotype has not well been connected with loss of functional mutation of CTNNB1 gene. Our finding expands the mutant spectrum of CTNNB1 gene and adds new understanding of the phenotype.